Radiation‐induced myofibroblastoma within the nasal sinus requiring maxillectomy and ethmoidectomy: A case report and literature review - David B. Meyer; Michael C. Larkins; Charles Klose; Mohammed Maher; Breann A. Zeches; Brian N. Brodish; Andrew W. Ju; Karyn Prenshaw (Clinical Case Reports, 2023)
Abstract We report a case of radiation‐induced myofibroblastoma of the right nasal cavity in a patient with a remote history of radiotherapy for pediatric retinoblastoma. The patient required maxillectomy and ethmoidectomy. To our knowledge, a rare number of cases have been reported in this location.